Digital Coaching Motivating Young Elderly People towards Physical Activity - Kettunen, Eeva; Kari, Tuomas; Frank, Lauri (MDPI AG, 2022)
The share of the elderly population is increasing globally, and it is important to help them to maintain their physical activity levels and ability to function to as late an age as possible. This qualitative intervention study focused on the experiences of young elderly on the ability of a sport and wellness technology digital coach to motivate them towards physical activity as well as on what needs and wishes this group has concerning digital coaching solutions. The findings of the study show that young elderly perceive digital coaching as potential in motivating them towards physical activity by providing instructive information and motivational feedback. It was also perceived to have positive influence on their exercise self-efficacy. However, it was also apparent that digital coaching devices should be tailored for this target group and be easy to learn in order to attract interest among them. Our findings provide insights for professionals and companies in sport technology field as well as to health professionals working in health promotion with young elderly people. Overall, this research aims to address social and economical sustainability of elderly people and their physical activity.
Keywords: digital coaching; exercise psychology; motivation; self-efficacy; sport technology; young elderly